Polar opposites? Marine conservation tools and experiences in the changing Arctic and Antarctic. (September 2016) - Wenzel, Lauren; Gilbert, Neil; Goldsworthy, Lyn; Tesar, Clive; Mcconnell, Martha; Okter, Melis
Abstract: The polar regions are undergoing vast changes in the land and seascape. They serve as major components of the Earth's climate system and are particularly vulnerable to climate change impacts. Warming temperatures, combined with increased human use and resource extraction, are putting increasing pressure on these vulnerable regions. While the Arctic and Antarctic are distinct from one another in their governance and human use, the 2014 World Parks Congress provided a platform for joint learning on progress and options for protecting marine areas in these unique regions. Though they remain among the remotest places on earth, their important role for global biodiversity, climate processes and economic activity have made them a focus for conservation efforts. Establishing a robust, integrated network of protected areas is one important tool for protecting ecosystem function and enhancing resilience as these regions face climate change impacts as well as increasing pressures for resource exploitation. This paper describes some major efforts to establish marine protected areas (MPAs) in the Arctic and Antarctic and analyses the similarities and differences in marine protection initiatives in the Earth's polar regions. As a basis for the analysis the authors focus on the following two themes: pressures – what are they and how fast are they growing; and governance – are there appropriate governance structures to establish and manage MPAs at appropriate geographic scales? Copyright © 2016 John Wiley & Sons, Ltd.